Treatment of peritoneal surface neoplasms with intraperitoneal chemotherapy in hyperthermia - Mielko, Jerzy; Ciaseł, Bogumila; Skórzewska, Magdalena; Sitarz, Robert; Kurylcio, Andrzej; Polkowski, Wojciech P. (Polish Journal of Public Health, 2015)
Effective treatment of peritoneal surface neoplasms is possible through the simultaneous use of cytoreductive surgery with intraperitoneal chemotherapy in hyperthermia. It is successfully performed in patients with peritoneal pseudomyxoma, mesothelioma, as well as a limited and resectable peritoneal carcinomatosis in the course of colorectal cancer. It can also be used in patients with gastric or ovarian cancer but also metastatic colorectal cancer or metastases to the ovaries from gastric cancer. Aggressive surgical management of patients with primary or secondary neoplasms of the peritoneal surface was initiated by Sugarbaker’s research group.